Prevalence of rapid response systems in small hospitals: A questionnaire survey. Issue 23 (11th June 2021) - Hosokawa, Koji; Kamada, Hiroki; Ota, Kohei; Yamaga, Satoshi; Ishii, Junki; Shime, Nobuaki
Abstract : Abstract: The rapid response system (RRS) was introduced for early stage intervention in patients with deteriorating clinical conditions. Responses to unexpected in-hospital patient emergencies varied among hospitals. This study was conducted to understand the prevalence of RRS in smaller hospitals and to identify the need for improvements in the responses to in-hospital emergencies. A questionnaire survey of 971 acute-care hospitals in western Japan was conducted from May to June 2019 on types of in-hospital emergency response for patients in cardiac arrest (e.g., medical emergency teams [METs]), before obvious deterioration (e.g., rapid response teams [RRTs]), and areas for improvement. We received 149 responses, including those from 56 smaller hospitals (⩽200 beds), which provided fewer responses than other hospitals. Response systems for cardiac arrest were used for at least a limited number of hours in 129 hospitals (87%). The absence of RRS was significantly more frequent in smaller hospitals than in larger hospitals (13/56, 23% vs 1/60, 2%; P < .01). METs and RRTs operated in 17 (11%) and 15 (10%) hospitals, respectively, and the operation rate for RRTs was significantly lower in smaller hospitals than in larger hospitals (1/56, 2% vs 12/60, 20%; P < .01). Respondents identified the need for education and more medical staff and supervisors; data collection or involvement of the medical safety management sector was ranked low. The prevalence of RRS or predetermined responses before obvious patient deterioration was ⩽10% in small hospitals. Specific education and appointment of supervisors could support RRS in small hospitals. Abstract : Supplemental Digital Content is available in the text